Survei Penggunaan dan Efek Suplemen yang Dirasakan oleh Petinju Amatir - Trisnar Adi Prabowo; Nevitaningrum; Septian Resi Wibowo, Moch.; Dwi Yulianto, Wahyu (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. To investigate type of supplement and amount of supplement used as well as the perceived effect and needs of boxers. Materials and methods. This research is a survey conducted from December 2022 to January 2023. The instrument used a questionnaire (google form).Boxers have 2 criteria, namely: 1) are still active as athletes and 2) have been champions at the provincial level with a total of 155 boxers, 116 male boxers and 39 female boxers. Results. 74 boxers used more than 1 type of supplement (48%), 81 boxers used only 1 type of supplement (52%). Type of supplement, Creatine 23 boxers (8.1%). Whey Protein 14 boxers (4.9%), Fat Burner 93 boxers (32.9%). BCAA 26 boxers (9.2%). Amino 12 boxers (4.2%). Multivitamins and minerals 114 boxers (40.7%). The effect felt, 22 boxers felt effect is